EFL Teachers' Perspectives on the Integration of ChatGPT in Writing Assessment - Meyasa, Kadek Yeyen; Luh Putu Artini; Ni Putu Era Marsakawati (Universitas Pendidikan Ganesha, 2024)
The existence of ChatGPT as a great technology development is considered as a teaching media used for providing immediate feedback in assessing students’ writing performance indirectly enhancing their writing skills as well. This study aimed to analyze EFL teachers’ perspective on the integration of ChatGPT in writing assessment. Qualitative approach was used as the research design of the current study. There were two English teachers who taught 11th grade students. They were selected by using purposive sampling. The data were obtained through observation, and semi-structured interview. Observation sheet and interview guide were used as the research instruments. The collected data were analyzed by conducting verbatim transcription and coding. The findings revealed that there were positive and negative perspectives given by the teachers. It was shown that the teachers were positively response due to the excitement of using ChatGPT in easing the feedback provision meanwhile the negative response revealed that the teachers expressed reservations about its validity. The ethical privacy issue, data protection, and prejudice were mentioned as the challenge due to its implementation. It was added that assessment effectiveness, immediate feedback, and assistance outside the classroom were acknowledged as the benefits of implementing ChatGPT. The study implicates to the educational assessment-based technology. Teachers are required to have proper training to face the integration of technology in their assessment since it can have an impact as well as challenges for them.